2020
DOI: 10.1097/tp.0000000000003338
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Lung Perfusion Improves the Inflammatory Signaling Profile of the Porcine Donor Lung Following Transplantation

Abstract: Background. Primary graft dysfunction and allograft rejection represent major caveats to successful lung transplantation. Reducing inflammation in donor lungs before transplantation may improve outcomes. Evidence exists that ex vivo lung perfusion (EVLP) can alter the donor lung environment, although the mechanisms remain unclear. This study aimed to characterize the inflammatory signaling profile of the lung following standard and EVLP transplant and delineate the immediate impact on the recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…25 Notably, we observed that the cell survival and proliferation profiles were not altered by our different perfusion procedures. Interestingly, upregulation of the antiapoptotic BCL2 and downregulation of the proapoptotic Bax proteins were found 24 h posttransplantation in pig lungs treated with EVLP as compared to in classically transplanted lungs, 4 indicating that the survival pathways induced upon EVLP have a prolonged effect even after transplantation.…”
Section: Discussionmentioning
confidence: 96%
“…25 Notably, we observed that the cell survival and proliferation profiles were not altered by our different perfusion procedures. Interestingly, upregulation of the antiapoptotic BCL2 and downregulation of the proapoptotic Bax proteins were found 24 h posttransplantation in pig lungs treated with EVLP as compared to in classically transplanted lungs, 4 indicating that the survival pathways induced upon EVLP have a prolonged effect even after transplantation.…”
Section: Discussionmentioning
confidence: 96%
“…Collectively, these molecular studies suggesting beneficial effects of EVLP on IRI‐derived inflammation, provide mechanistic insights for various experimental studies that have demonstrated positive effects of EVLP on lung function after transplantation. Hence, porcine lungs transplanted using an EVLP showed a significantly lower acute lung injury score with less interstitial and intra‐alveolar edema, hemorrhage and hyaline formation when compared to lungs procured in the standard of care cold storage group 33 . Moreover, alveolar epithelial cell tight junction integrity, evaluated by zona occludens‐1 protein staining, had been preserved in the cell membranes of porcine lung tissue after EVLP 69 (Figure 1F).…”
Section: Evlp Improves Lung Function In Experimental Studiesmentioning
confidence: 91%
“…33 In turn, pro-survival signaling proteins had been upregulated in the EVLP transplanted pig lung (compared with the standard of care) including, ERK1/2, FAK, PDGFRβ, STAT5/6, and members of the Src family of protein tyrosine kinases Fgr, Hck, and Lck indicating cellular proliferation. 33 Consistently, after the third hour of acellular normothermic EVLP of clinically rejected human lungs, the strongest predicted activation in a gene expression array had been cell viability and cell survival in addition to a cellular tight junction recovery seen by upregulation of the tight junction canonical pathway 67 which was confirmed in another study using immunohistochemistry. 69 Further underscoring the concept of tissue repair, EVLP of explanted rat lungs has been shown to modulate the pulmonary turnover of high molecular weight hyaluron (Figure 1E), a tissue protective glycosaminoglycan contributing to the maintenance of lung tissue homeostasis.…”
Section: E Vlp Promote S Tissue Homeos Ta S Ismentioning
confidence: 99%
See 1 more Smart Citation
“…EVLP was introduced to the clinic in 2011 for high-risk lungs (290). Preclinical studies in a porcine model have shown that EVLP may reduce IRI by decreasing the insult on the endothelium or by reducing the inflammatory cytokine load (291)(292)(293). Controlling reperfusion by means of reversing oxygen debt in the absence of mechanical stress/strain and in the absence of platelets and neutrophils are also beneficial attributes of EVLP (291,292).…”
Section: Lungmentioning
confidence: 99%